Bakteri Indigen Pendegradasi Hidrokarbon Minyak Bumi di Kabupaten Siak Provinsi Riau - Riryn Novianty; Saryono; Awaluddin, Amir; Wahyu Pratiwi , Nova (Talenta Publisher (Universitas Sumatera Utara), 2020)
The process of producing, refining and transporting petroleum can cause pollutants that are harmful to the environment and the living things that surround them. Indigenous microorganisms can be a solution to degrade hydrocarbons that are difficult to degrade. This study aims to isolate the indigenous bacteria from pollutant-contaminated soil and test its effectiveness in degrading hydrocarbons. The research began with soil sampling at the Joint Operating Agency of PT Siak Bumi Pusako-Pertamina Hulu Siak Regency, Riau Province with a purposive sampling method. The next step is the isolation of indigenous bacteria, testing the parameters of pH, Optical density (OD) and CO2 levels during the 16 incubation periods and determining the highest percentage of biodegradation. The results showed that Pseudomonas sp. with a code BTM2 (Bakteri Tanah Minyak 2) had the largest percentage (52.20%) after 16 days of incubation under optimum conditions to degrade the total hydrocarbon of petroleum. Pseudomonas sp. BTM2 is the most effective isolate to degrade hydrocarbons.